أزمة الهوية الجنسية لدى الشباب الجزائري وانعكاساتها على التقمص السوي للأدوار الأبوية - لحمر, فضيلة (Changement Social, 2018)
إن دراسة موضوع مهم مثل تغير الأدوار في الأسرة يستلزم الإحاطة الشاملة من كل النواحي سواء كانت اجتماعية أو اقتصادية أو نفسية، ويعتبر إعداد الأسرة عملية مستمرة تبدأ منذ مراحل النمو الأولى أين يكون للتقمص دور كبير لدى الفرد في تشكيل الصور الأبوية السوية، وتعد مرحلة الشباب من أهم مراحل النمو النفسي التي حددها اريك اريكسون، والتي ضمنها وجود أزمة هوية، يقع فيها الشاب، ومن أهم عناصر هاته الأزمة ، مشكلة الهوية الجنسية، حيث  يعتبر اريك اريكسون أن حل أزمة الهوية الجنسية هو المفتاح الأساسي للتقمص السوي للأدوار الأبوية في المستقبل، مما يجعل الشاب في مرحلة الرشد المبكر قادر على تحديد واختيار الشريك المناسب لتكوين أسرة سوية.     منذ سنوات خلت لم يكن موضوع أزمة الهوية الجنسية  واضحا في مجتمعاتنا المحافظة والتي تساهم بفعل الجوانب الروحانية والإيمانية في خلق تقمص سوي للأدوار الجنسية، ولكن للأسف مع الانفتاح التكنولوجي الكبير وعصر العولمة، أصبحنا نلاحظ مظاهر جديدة لنمط علاقات بين الجنسين مختلفة نوعا ما،  لقد شرعت بعض الأنظمة الدولية الشذوذ الجنسي وأعطت المثلين نفس الحقوق والوظائف، كما أعطتهم الحق في الزواج وتكوين اسر مشوهة غير سوية، إن انعكاس مثل هاته التطورات على البيئة المحلية قد يكون خطيرا جدا، خلال هاته المداخلة نسلط الضوء على أهمية حل أزمة الهوية الجنسية،  قبل مرحلة الرشد المبكر وعلى أهم مظاهرها داخل مجتمعنا وعلى مدى تأثر شبابنا بالمفاهيم والأدوار الجنسية العالمية الجديدة ـ وكيف تنعكس على مستقبل اختياراتهم الزوجية وتقمصهم للأدوار الأبوية . The study of an important topicsuch as roles change in the family, requires a comprehensive briefing from all aspects, whether social, economic or psychological, is a familypreparing a continuousprocessstartingfrom the early stages of growthWhereis the reincarnation of a greatrole of the individual in shaping the image of patriarchal normal, and longer youngadulthood of the most important psychologicaldevelopment stages defined by Erik Erikson, Yearsagowas not the subject of the identitycrisis of sexual and clear in our province and thatcontribute by spirituality and faith aspects of creating a reincarnation of normal sexualroles, but unfortunatelywith the greattechnologicalopenness and the era of globalization, we note a new manifestation of the pattern of relationshipsbetweendifferent sexes somewhat, it has embarked on somehomosexuality international regulations and given the samerights and functions, sexuallydeviantAlso gave them the right to marry and startfamilies of deformed, abnormal, if the reflection of suchdevelopments on the local environmentmaybeverydangerous, throughthis intervention to highlight the importance of resolvingsexualidentitycrisis, by earlyadulthood and the most important manifestations withinour society and on the vulnerability of ouryouth new concepts of global citizenship and roles, and how theyreflect on the future of theirchoices and marital reincarnation of parental roles.